Survival and development of Scylla serrata larvae with formalin and trifluralin against fungal infection - Tillo, Jennette D. (University of the Philippines in the Visayas, 2007)
The study was conducted to determine the efficacy of prophylactic doses of formalin and trifluratin against Lagennidium fungal infection in mud crab larvae through toxicity, prolonged prophylactic treatment, pathogenicity and challenge test of infected larvae. Toxicity was assessed on the basis of survival of larvae after 24, 48,72 and 96 h exposure to the test chemicals and metamorphosis to the next larval stage. Larval survival in all stages was significantly (P<0.05) reduced at concentrations of 20 and 25 ppm formalin whereas larvae were able to tolerate all trifluralin treatments. However, larvae became more tolerant to high formalin concentrations as the larval stage progressed. Enhanced survival was observed at 5, 10 and 15 ppm formalin and in all trifluralin treatments compared to controls in almost all of the larval stages. Improved metamorphosis to the next larval stage was observed in 5 and 10 ppm formalin and 0.05, 0.1 and 0.2 ppm trifluralin cncentrations. Doses of formalin and trifluralin obtained from the toxicity experiments were applied every other day as prophylaxis to newly hatched larvae in white plastic basins. Prophylactic dose of 5 and 10 ppm formalin and 0.05 and 0.1 ppm trifluralin applied every other day were found to give better survival and larval development to megalopa compared to control. However, no megalopae survived to crab instar in all formalin treatments. Trifluralin treatments consistently gave higher survival rates and enhanced metamorphosis compared to formalin treatments. A fungus belonging to order Lagenidiales was identified based on the morphology of the hypha, formation of vesicles and spore release. The fungus was used in experimental infection of mud crab zoea 1 and 2 where highest mortality was observed in larvae inoculated with 10 3 spore/ml. Spore concentrations of 10 1 and 10 2 spore/ml were also pathogenic to S. serrata larvae. Prophylactic doses of 0.1 ppm trifluralin and 10 ppm formalin were found suitable for Lagenidium infection in the pathogenicity test as improved survival and less fungal infection was observed in these treatments. Fungal infection in control groups indicated that fungus may have been present during the embryonic stage, hence, chemical treatment is necessary to prevent or minimize fungal infection in the larviculture of mud crab. although the use of fungicides in rearing systems resulted to higher survival and enhanced metamorphosis compared to controls, other techniques should be further investigated as an alternative to the use of chemicals in hatcheries.